Molecular Docking and Molecular Dynamics Analysis of Phytochemical Compounds from Nutmeg Fruit (Myristica fragrans Houtt.) on Androgen Receptor (4K7A) as Anti-Alopecia Therapy - Yasir, Angga Saputra; Sari, Indah Puspita (Jurnal Kimia Fullerene, 2025)
Androgenetic alopecia (AGA) represents the most prevalent hair loss form, necessitating natural treatment alternatives. This study investigated nutmeg (Myristica fragrans Houtt.) phytochemicals as anti-alopecia agents through molecular docking and dynamics simulations. Thirty-four compounds, including native ligands (minoxidil, finasteride) and 32 nutmeg-derived compounds, were evaluated against androgen receptor (PDB: 4K7A) using AutoDock4.0 and GROMACS 2024.2. Molecular docking validation achieved successful minoxidil redocking with 2.25 Å RMSD, confirming method reliability. Geranylgeraniol (ID: 33) demonstrated optimal results with -7.00 kcal/mol binding energy, nearly equivalent to finasteride (-7.19 kcal/mol) and superior to minoxidil (-4.85 kcal/mol). Geranylgeraniol formed strong hydrogen bonds with GLU793 at 1.77 Å distance, with nearby residues LEU862, TYR857, ARG854, LYS861, and LEU797. Twenty-five nanosecond molecular dynamics revealed stable complex formation with 0.23-0.25 nm RMSD values, indicating acceptable binding stability. RMSF analysis showed geranylgeraniol induced higher structural flexibility in specific regions, potentially enhancing biological activity. SASA analysis demonstrated lower surface area values (112.5 nm²), indicating improved stability versus minoxidil. These findings suggest geranylgeraniol possesses significant anti-alopecia potential with comparable finasteride efficacy and superior minoxidil performance.